Analysis of Visual Elements in the Poster for the Film “Panggil Aku Ayah” - Mahdum, Alpaka Fachrudin; Hidayatullah, Taufan; Ekawardhani, Yully Ambarsih (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
Film posters play a strategic role as a medium of visual communication; however, academic studies on the visual meaning of Indonesian film posters remain limited. This study aims to analyze the visual elements of the film poster “Panggil Aku Ayah” in order to reveal the symbolic meanings constructed through its visual elements. This study uses Ferdinand de Saussure’s semiotic approach, which views a sign as a unity between the signifier as the perceptible physical form and the signified as the concept of meaning produced. The results show that orange sans-serif typography represents emotional warmth, the illustration of three characters symbolizes family bonds, the color combination conveys optimism and simplicity, and the vertical layout constructs a directed visual narrative flow. These four elements work synergistically to convey that the visual elements of the poster successfully construct symbolic meanings that support the film’s narrative. These findings demonstrate the effectiveness of Saussurean semiotics as a framework for analyzing visual communication in film posters, while also providing practical implications for graphic designers in designing film promotional materials.